Residential rooftop solar panel adoption behavior: Bibliometric analysis of the past and future trends - Muhammad Ashraf, Fauzi; Nazim Hanis, Zainal Abidin; Norazah, Mohd Suki; Budiea, A. M. A.
This study reviews residents' behavioral adoption of rooftop solar photovoltaics (solar PV). Solar PV imparts many benefits towards the environment, economic and social development. However, there has been no comprehensive understanding of knowledge structure in solar PV adoption among households in the literature. Through a bibliometric approach, 564 publications on residents’ adoption of solar PV were retrieved from the Web of Science (WoS). A co-citation and co-word analysis were performed to uncover past and predict future trends in this regard. The analysis produces significant themes related to residents' diffusion innovation adoption and motivation/predictors toward solar PV. This review contributes to the fundamental understanding of residents' critical determinants of solar PV adoption. Theory and practical implications are discussed.